2021
DOI: 10.4049/jimmunol.1900656
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 through Aryl Hydrocarbon Receptor Regulates IL-22 Response in CD4+ T Cells

Abstract: IL-17A and IL-22 derived from Th17 cells play a significant role in mucosal immunity and inflammation. TGF-β and IL-6 promote Th17 differentiation; however, these cytokines have multiple targets. The identification and screening of additional molecules that regulate IL-17A and IL-22 responses in certain inflammatory conditions is of great clinical significance. In this study, we show that CDDO-Im, a specific Nrf2 activator, promotes IL-17A and IL-22 responses in murine Th17 cells. In contrast, CDDO-Im inhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…S2 D ). In addition to STAT3, nuclear factor-erythroid 2-related-2 (Nrf2) can also transactivate AhR expression ( 25 , 26 ). We found that although hardly detectable in naive T cells, Nrf2 was rapidly up-regulated in T eff cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2 D ). In addition to STAT3, nuclear factor-erythroid 2-related-2 (Nrf2) can also transactivate AhR expression ( 25 , 26 ). We found that although hardly detectable in naive T cells, Nrf2 was rapidly up-regulated in T eff cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are studies about whether IL-17 could serve as biomarkers for cancer; however, the results have been controversial. In the field of lung cancer studies, it has been reported that the expression level of IL-17 is elevated in the serum of patients, and the level of IL-17 in the serum of the patients may function as a prognostic marker, 15 , 22–24 while on the other hand, some other studies had shown that the levels of IL-17 did not show differences between the patients and healthy controls. In the present study, we observed that the serum level of IL-17 was significantly upregulated in the serum of the patients in comparison with the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tBHQ induced an Nrf2-dependent increase in IgM secretion by LPS-stimulated B cells ( 106 ). Meanwhile, studies have shown that Nrf2 can regulate the IL-22 response in CD4 + T cells through the AhR pathway ( 107 ). This suggests that activation of Nrf2 has a relevant role in regulating both T and B cells.…”
Section: The Role Of Nrf2 In Ulcerative Colitismentioning
confidence: 99%